Tensile testing for weld deformation properties in similar gage tailor welded blanks using the rule of mixtures - Abdullah, Kassim Abdulrahman; Wild, P M; Jeswiet, J J; Ghasempoor, A (Elsevier, 2001)
A method for measuring the properties of laser weld metal in tailor welded automotive blanks is assessed. Tensile specimens in which the weld lies parallel to the axis of tension are pulled to failure and the weld metal properties are determined using a "rule of mixtures" type of calculation. Experiments are performed using two sets of similar gage welded steel specimens. The sensitivity of determined weld metal properties to specimen size and means of determination of weld metal cross-sectional area are assessed. The method is shown to be useful but in need of refinement, especially with respect to the measurement of weld metal cross-sectional area.